2014
DOI: 10.1037/a0034302
|View full text |Cite
|
Sign up to set email alerts
|

How experts practice: A novel test of deliberate practice theory.

Abstract: Performance improvement is thought to occur through engagement in deliberate practice. Deliberate practice is predicted to be challenging, effortful, and not inherently enjoyable. Expert and intermediate level Gaelic football players executed two types of kicks during an acquisition phase and pre-, post-, and retention tests. During acquisition, participants self-selected how they practiced and rated the characteristics of deliberate practice for effort and enjoyment. The expert group predominantly practiced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 45 publications
0
41
1
Order By: Relevance
“…Rheinberg and Engeser, 2010 as well as Christophel et al, 2014, for training of motivational competence). Underlining this challenge, Coughlan et al, 2014 reported that participants in the expert group of their study rated their practice as more effortful and less enjoyable compared to other participants. The experts were successful in improving performance, by predominantly practicing the skill they were weaker at.…”
Section: Discussionmentioning
confidence: 99%
“…Rheinberg and Engeser, 2010 as well as Christophel et al, 2014, for training of motivational competence). Underlining this challenge, Coughlan et al, 2014 reported that participants in the expert group of their study rated their practice as more effortful and less enjoyable compared to other participants. The experts were successful in improving performance, by predominantly practicing the skill they were weaker at.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to remedy concerns about the reliability of retrospective DP activity ratings, Coughlan, Williams, McRobert, and Ford (2013) recently employed a novel paradigm where they collected in situ ratings of Gaelic football players' practice activity. In a laboratory setting, investigators first confirmed that the practice trials in which experts and intermediates engaged had indeed improved performance (i.e., they ensured relevance of the practice using pre-to-post analyses and retention tests).…”
Section: Habits Of Elite Performers 2: Periods Of Deliberate Practicementioning
confidence: 99%
“…Such an approach is especially important when studying expert learning, where subtleties in processes may be more evident following practice than (positive) changes in behavioural outcomes. Moreover, there is a paucity of research where verbal reports have been gathered on a pre-test as well as on subsequent retentionand transfer-tests (for an exception, see Coughlan et al, 2014). Whilst kinematic measures are commonly employed on simple tests of motor skill learning, detailed motion analysis is less common for the acquisition of more complex skills, such as those involved in sport.…”
Section: 2mentioning
confidence: 99%
“…The need to be able to draw firmer inferences about causality may necessitate moving away from retrospective, historical accounts of practice (i.e., the 'bean counting' approach) towards more prospective approaches combining some of the tenants of deliberate practice theory with more traditional, quasi-experimental designs. A published report by Coughlan, Williams, and Ford (2014) nicely illustrates how the tenants of deliberate practice may be studied under controlled conditions involving a traditional learning design, including measures of transfer and retention, and process measures of learning. The need remains to specify not just how much deliberate practice occurs amongst learners, but also how deliberate the learners are during practice itself.…”
Section: Tracing the Development Of Expert Learnersmentioning
confidence: 99%
See 1 more Smart Citation